Diel variations in the photosynthetic parameters of Prochlorococcus strain PCC 9511: Combined effects of light and cell cycle - F. Bruyant; M. Babin; B. Genty; O. Prasil; M. J. Behrenfeld; H. Claustre; A. Bricaud; L. Garczarek; J. Holtzendorff; M. Koblizek; H. Dousova; F. Partensky (Limnology and Oceanography, 2005)
We examined the mechanisms related to the diel variations in the parameters of the relationship between the rate of carbon fixation of phytoplankton and irradiance ( P vs. E curve). Our goal was to understand what determines the phase of these variations relative to that of the light cycle. We grew the marine prokaryote Prochlorococcus in an axenic cyclostat culture system under a light–dark cycle that mimicked natural conditions at sea surface and followed changes in cell physiology with a 2‐h resolution. Individual cells divide mostly in phase with each other, once a day at the beginning of the dark period. The quantum yields of chlorophyll fluorescence, the maximum quantum yield of carbon fixation (φ Cmax ) and the maximum rate of carbon fixation (P B max ) exhibited diel variations over about factors of 2, 4, and 4, respectively, with maxima at the beginning of the light period. The morning drop in φ Cmax and the quantum yield of fluorescence, which was accompanied by only a small decrease ( F v / F m ), suggests regulation by light and preceded the drop in P B max by 4 h. The decrease in P B max during the day matched a decrease in the transcription level of Rubisco. The quantum yield of fluorescence, φ Cmax , and P B max increased again during the dark period, but this recovery was slowed at the time of cell division. Our results suggest that the pattern of diel variations in the photosynthetic parameters is determined both by photoacclimation and the cell‐division cycle.

Synchronized expression of ftsZ in natural Prochlorococcus populations of the Red Sea - Julia Holtzendorff; Dominique Marie; Anton F. Post; Frédéric Partensky; Assaf Rivlin; Wolfgang R. Hess (Environmental Microbiology, 2002)
Summary The expression of ftsZ , encoding the initiating protein of the prokaryotic cell division was analysed in natural Prochlorococcus populations in the Gulf of Aqaba, northern Red Sea. During the seasonal Prochlorococcus bloom in September 2000, picoplankton was collected from the deep chlorophyll maximum (DCM) at 2–4 h intervals over 3 consecutive days. Flow cytometric measurements as well as DNA sequence analyses showed that Prochlorococcus was the dominant photosynthetic organism. Cell densities peaked as high as 1.4 × 10 5 cells ml −1 . This DCM population mainly consisted of brightly red fluorescing Prochlorococcus cells, corresponding to low light‐adapted ‘ecotypes’ ( sensu Moore et al ., 1998, Nature 393: 464–467). Prochlorococcus populations grew in a highly synchronized fashion with DNA replication in the afternoon and cell division during the night. The ftsZ mRNA level reached maximum values within the replication phase between 14.00 and 16.00 hours, and minimum values between 02.00 and 06.00 hours. Thus, the transcriptional regulation of ftsZ could be a major factor triggering the synchronized cell division of Prochlorococcus populations. This is the first application of quantitative reverse transcriptase‐coupled real‐time polymerase chain reaction (PCR) to natural populations of an environmentally relevant marine organism.

An axenic cyclostat of Prochlorococcus PCC 9511 with a simulator of natural light regimes - F. Bruyant; M. Babin; A. Sciandra; D. Marie; B. Genty; H. Claustre; J. Blanchot; A. Bricaud; R. Rippka; S. Boulben; F. Louis; F. Partensky (Journal of Applied Phycology, 2001)